Inadequate completion of surgical data for patient safety: opinion of health professionals - Almeida, Anny Caroline Santos (2021)
Objective: to investigate variables related to inadequate completion of surgical data for patient safety in the hospital setting in the opinion of health professionals. Methods: retrospective study in 180 medical records of surgical patients in a public hospital and application of a structured questionnaire to caregivers responsible for filling out the surgical data of patients. Descriptive statistical analysis was performed. Results: the medical records showed incomplete surgical records in the preoperative period (61%), intraoperative period (66%) and immediate postoperative period (87%). Professionals reported not knowing the protocol for safe surgery (62%) and the institution's surgical safety form (68%), 87% were not trained to use the intraoperative checklist, 66% considered the number of staff inadequate and 55% considered communication ineffective. Conclusion: in the opinion of health professionals, insufficient professional knowledge, lack of training, inadequate staffing and ineffective communication may be related to inadequate completion of surgical data and patient safety.